The Strategic Role of Community Policing and Motorcycle Theft Prevention in Indonesia Font - Natassja Yvonne, Gloria (Jurnal Ilmu Kepolisian, 2025)
Motorcycle theft cases in Indonesia have increased throughout the year. Efforts have been made to reduce motorcycle theft crimes. However, these efforts have not been successful due to various factors, one of which is the limited effectiveness of community policing in Indonesia, largely attributed to a lack of openness and public trust in police cooperation. Through a literature analysis, the police must serve, protect, be transparent, and offer community counseling to ensure that community policing in Indonesia functions efficiently and effectively. Then, through the combination of two policing models, such as hot spot policing and e-policing, it is intended that community policing in Indonesia would be able to effectively reduce the number of motorcycle theft crimes, and the cooperation and partnerships that have been built and established previously can be appropriately maintained.